A Free Enterprise and Autonomy Private in Tax Law: Tax Evasion and Avoidance and Tax Planning Versus art. 116, paragraph, of CTN - Caminhoto, Rita Diniz (2015)
The principles of free enterprise and private autonomy are basic the Federative Republic of  Brazil. Through the private autonomy, the State grants the human being in society, the power to act at will, since according to the precepts of the law. He can hire, finally, perform all acts and legal transactions allowed by law. The taxpayer has the right to seek less expensive ways to make their economic activities, such as the adoption of so-called resource tax planning to achieve profit and reduce the tax burden. This work aims to study the avoidance and tax evasion, simulation, dissimulation, fraud to the law, abuse of law and order, to be able to play if given tax planning in this case it is lawful or not, understand the doctrines business purpose doctrine, substance over form doctrine and step transaction doctrine and find what position was adopted by the Brazilian legal system, on the classification of tax planning in licit or illicit, and provides the views of various authors about which of them should be applied to the understanding of the provisions of the sole paragraph of article 116, of CTN. As methods adopted for the preparation of this paper, deductive employees, systems and axiological, using literature, stating the legal doctrine, scientific articles, case law and the Brazilian legal system, as the Federal Constitution of 1988, the Code National Tax. The problems and the justification of this scientific article refers to differences in interpretation of the sole paragraph of art. 116, from CTN, in relation to legal forms adopted in tax planning by companies on behalf of the principles of free enterprise and private initiative, whether such a standard is considered not avoidance or not evasion. Seeks to understand the figures of tax avoidance and tax evasion, simulation and concealment, abuse of form and law. So, these are the issues addressed in this work in order to put into perspective the tax law and understand the controversy of tax planning.